Relationship between serum levels of β2-microglobulin and left ventricular structure and function in maintenance hemodialysis patients - SU Jun; SUI Gui-qin; LI Hao; TIAN Fang; QIU Fang-xin (Linchuang shenzangbing zazhi)
Objective To explore the role of serum β2-microglobulin( β2-MG) levels in predicting left ventricular hypertrophy( LVH) in maintenance hemodialysis( MHD) patients by retrospectively investigating the serum levels of β2-MG and changes in cardiac structure and function,and analyze the relationship between β2-MG with left ventricular structure and function. Methods Totally 147 MHD patients in Blood Purification Center of Qingdao Chengyang People’s Hospital from January 2016 to June 2016 were selected.According to the inclusion and exclusion,71 MHD patients were enrolled in this study. LVH was diagnosed when both left ventricular wall thickness( LVPWT) and interventricular septum thickness( IVST)were ≥12 mm. The subjects were divided into LVH group and non-LVH group. Serum β2-MG levels were measured by ELISA. Cardiac structure and function were assessed by two-dimensional echocardiography.Results The serum levels of β2-MG and C reactive protein in MHD patients with LVH were significantly higher than in those without LVH( P < 0. 05). The left ventricular diameter( LVD),left atrial diameter IVST and LVPWT were significantly higher,and the left ventricular ejection fraction( LVEF) was significantly lower in MHD patients with LVH( P < 0. 05). β2-MG levels were positively correlated with LVD and LVPWT( P < 0. 05),but negatively with hemoglobin( P < 0. 05). Multiple regression results showed that LVD,LVPWT and hemoglobin were associated with β2-MG levels independently( P < 0. 05). Conclusions Elevated levels of β2-MG in MHD patients had a relationship with cardiac structure and function,which may play a key role in the occurrence of cardiovascular events. This study suggests that serum β2-MG levels may be helpful in predicting the severity of LVH in MHD patients.